Seeing Albertine Seeing: Barbey and Proust Through Balzac - Dorothy Kelly (Studies in 20th & 21st Century Literature, 1990)
The three texts, Balzac's La Fille aux yeux d'or, Barbey d'Aurevilly's Le Rideau cramoisi, and Proust's La Prisonnière, share two structuring themes: the problematic eyes of a woman who desires, and the need to see the woman in order to learn her truth. This article first does a close reading of these themes in the texts. Second, the difference between Barbey and Proust is examined in their ultimate conclusions about the truth of woman, and Proust's text is studied in its use of the impossibility of truth as the origin of its fiction.
Keywords: Balzac; La Fille aux yeux d' or; Barbey d' Aurevilly; Le Rideau cramoisi; Proust; La Prisonnière; woman; truth; fiction; man; desire